THE POSSIBLE TECHNOLOGICAL VARIANTS OF MELTING OF ZINC ALLOYS OUT OF SECONDARY RAW MATERIALS - A. M. Galushko; V. M. Korolev; A. G. Slutskij; A. A. Galushko; A. N. Stepanuk (Литьë и металлургия)
The technology of metallurgical recycling of zinc scrap for bar alloys including high-strength ones with increased contents of aluminum and copper is offered.